Analysis of the Competitiveness of Sago-Based Pastry Products: Case Study of the Meambo Food Sago Business Group in Kendari City - Maharani, Hilda Amalia; Iswandi, Marsuki; Taridala, Sitti Aida Adha (International Journal of Technology and Education Research, 2025)
This study aims to determine 1) the volume of raw material use for sago products, and 2) the competitiveness of sago products in Kendari City. This research was conducted in Purirano Village, Kendari District, Kendari City, Southeast Sulawesi Province, specifically in the Sago Meambo Food Business Group (KU-SMF), which produces processed sago agricultural products in several variants, including chocolate sago biscuits, chocolate sago brownies, beng-beng sago, and moringa leaf sago chips. The research was conducted in May 2024. Competitiveness analysis was carried out using PAM (Policy Analysis Matrix) analysis, which aims to determine whether a policy can improve competitiveness for a business that is generated through the creation of business efficiency and revenue growth. The results of the study showed that 1) Krispi Brownis Sago uses various ingredients in relatively large quantities, especially sago flour, indicating that this product has a dense structure and significant main ingredients. The same selling price as other products, but with the use of more varied materials reflects the balance between costs and selling prices. 2) The Sago Meambo Food Business Group has comparative advantages and competitive advantages. The Sago Meambo Food Business Group has efficiently used its domestic resources at international prices and is able to finance its domestic factors at actual prices